Being a deliberate prey of a predator: Researchers’ thoughts after having published in predatory journal - Shaghaei, Najmeh; Wien, Charlotte; Holck, Jakob Pavl; Thiesen, Anita L.; Ellegaard, Ole; Vlachos, Evgenios; Drachen, Thea Marie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
A central question concerning scientific publishing is how researchers select journals to which they submit their work, since the choice of publication channel can make or break researchers. The gold-digger mentality developed by some publishers created the so-called predatory journals that accept manuscripts for a fee with little peer review. The literature claims that mainly researchers from low-ranked universities in developing countries publish in predatory journals. We decided to challenge this claim using the University of Southern Denmark as a case. We ran the Beall’s List against our research registration database and identified 31 possibly predatory publications from a set of 6,851 publications within 2015-2016. A qualitative research interview revealed that experienced researchers from the developed world publish in predatory journals mainly for the same reasons as do researchers from developing countries: lack of awareness, speed and ease of the publication process, and a chance to get elsewhere rejected work published. However, our findings indicate that the Open Access potential and a larger readership outreach were also motives for publishing in open access journals with quick acceptance rates.